Explaining Local Tax Compliance through Behavioral and Institutional Perspectives: The Role of Quality Interaction and Adaptive Governance - Kadek Ayu Silvia Yuliaratih; Ida Ayu Oka Martini; Agus Fredy Maradona (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Taxpayer compliance continues to pose a significant challenge in local tax administration globally, including in Indonesia. This review seeks to redefine local tax administration by incorporating three perspectives: social psychology, organizational design, and strategic governance. This study aims to explain the dynamics of local tax compliance through behavioral and institutional approaches and to identify ways to make local tax administration more effective through quality interactions and adaptive governance systems. The study employs a systematic literature review with a conceptual and thematic synthesis approach to examine relevant studies on local tax compliance and administration. The findings indicate that taxpayer compliance is influenced not only by legal and economic factors but also by social-psychological behavior, institutional capacity, and governance legitimacy. Compliance is particularly shaped by interaction quality between taxpayers and tax officers, administrative modernization, and collaborative, transparent governance. This study proposes an Adaptive Local Tax Compliance Framework that balances behavioral legitimacy, institutional capacity, and governance accountability. The findings suggest that local governments should shift from control-centric models toward collaborative, trust-based approaches to enhance compliance and administrative effectiveness, contributing to the literature by integrating behavioral, institutional, and governance perspectives in local tax administration.